Kontribusi Positif Wisata Alam dan Kearifan Budaya Lokal Suku Besemah di Kota Pagaralam terhadap Wisatawan dan Masyarakat Lokal - Natasya Syahirha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The natural tourism and cultural arts greatly affects the interest of tourists to enjoy natural attractions and learn about the local art and culture of the Besemah tribe. Its tourist destinations offer a green concept to its natural tourism and provide a unique experience to its local arts and culture. This article aims to dig deeper into the influence of natural tourism and local cultural arts and can find out what aspects affect tourist interest. Through this analysis, it is hoped that it can be understood how natural tourism and cultural arts of the Besemah tribe can influence tourist interest and review related to tourist development. In addition, this article also explains how the impact of natural and cultural tourism affects the economy of local communities. This article was written through a descriptive qualitative method in the form of non-participant observation. The results of the research contained in the article are the great influence of natural tourism and local cultural arts of the Besemah tribe on the interest of the tourists because of the beauty, philosophy behind art and culture, as well as Besemah's typical handicrafts that can be used as souvenirs from Besemah and have an economic impact on the local community. Therefore, there is a need for a form of awareness for local and foreign communities to maintain and preserve nature and cultural arts and continue to improve development so that natural tourism and cultural arts can be known abroad and benefit the local community.